ANALISIS TERJADINYA SCALING SILICA PADA CONDENSER DAN COOLING TOWER - Priskilla Wulandari Polimpung; Heinrich Taunaumang; Jeferson Polii (Jurnal FisTa : Fisika dan Terapannya, 2021)
Silica scaling in geothermal production fields can clog the fluid flow rate. Research has been conducted to determine the occurrence of scaling sillica in brine. The method used in processing this data is by using an application in the form of steam tables and Microsoft Excel. Therefore, a study of the potential for silica scaling in activities that utilize geothermal energy is needed. In this study, a study on the potential for silica scaling in a geothermal power plant in the Lahendong area unit 2 cluster 13.The purpose of this study was to estimate the possibility of scaling silica in the condenser and cooling tower in the geothermal field. After the research was carried out, it could be concluded that the results of the calculation of scaling sillica in the Lahendong geothermal field were the condenser at 11.2 ppm while cooling tower was 72.5 ppm. When silica concentration in this field is compared with the calculated silica concentration, the silica will not settle in the condenser or the cooling tower.This is because the silica concentration in the field is smaller than the calculated silica concentration, so there is no silica scaling at the inlet or outlet of condenser and cooling tower.